Vocational Pedagogical Decisions of Malaysian and Indonesian Non-Engineering TVET Teachers - Yunos, Jailani Md; Rubani, Siti Nur Kamariah; Alias, Maizam; Sumarwati, Sri; Yunus, Faizal Amin Nur; Hamid, Hashima; Rizal, Fahmi (Journal of Technical Education and Training, 2019)
A teacherâ€™s pedagogical decisions determine the quality and effectiveness of the teaching and learning process while academic content (practical or theories), as well as teachers cultural background (as indicated by teacher’s nationality), can influence teachersâ€™ decision makings. Thus, the aim of this study was to identify the dominant pedagogical decisions as practiced by non-engineering TVET teachers in two countries namely Malaysia and Indonesia. A survey was conducted on 312 Malaysian Vocational College (VC) and 200 Indonesian Vocational Senior Secondary School (VSSS) teachers. A questionnaire consisting of 33 items on pedagogical decisions was used to gather data on teacherâ€™s pedagogical decisions. Descriptive analysis conducted on the data indicate that the findings indicate that there are similar in vocational pedagogical decisions used by Malaysian-Indonesian respondents based on "Role of Teacher", "Nature of Knowing", "Organization of Time", "Content of Curriculum", "Organization of Space", "Approach to Task" and "Visibility of Processes". In addition, this study found that there are differences in vocational pedagogical decisions used by Malaysian-Indonesian non-engineering TVET teachers based on "Attitude to Knowledge", "Proximity to Teacher" and "Role of Learner".